“Teaching religion”. (Journal of Parents and Teachers, 2014)
What is teaching religion? This broad expression causes many misunderstandings which, through three frames, are intended to clarify: the model of giving religion as teacher and evangelizer, the levels and possibilities of the subject and the aspects that religion adds to a humanistic education of quality.
Keywords: Religion; give religion; evangelize; pictures; clarify.